(untitled) (Annual of the Faculty of Philosophy in Skopje, 2012)
Risk is a move to implement the western liberal system in countries which have liberal tradition. Establishing liberal democratic principles and values by using military means proved unsuccessful and often turn into an ideology of domination over countries opponents of the West. Manipulations with information from the U.S. side connected to the Iraq war left suspicions which for a long time points are reflected on their foreign and security policy. The attempt by forced to opening Iraq toward the world in order to establish new forms of cooperation, leading to fragmentation of the country on various grounds, for its contribution to the marginalization of various world happenings and triggered fierce competitions among participants for exploration of natural resources.